2007
DOI: 10.1016/j.compag.2007.01.014
|View full text |Cite
|
Sign up to set email alerts
|

SeedChaser: Vertical soil tillage distribution model

Abstract: Knowledge of the vertical distribution of surface residues, chemicals, or seeds following tillage operations is of great importance to a wide variety of soil research areas. This paper describes a 1D empirical vertical soil tillage distribution model with 1 cm grid spacing (SeedChaser) that predicts vertical redistribution of weed seeds following user selected (a) sequences of tillage implements, and (b) initial seed distribution values. Results of this model are particularly suited for weed seed emergence mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 36 publications
(36 reference statements)
1
33
0
2
Order By: Relevance
“…Soil tillage is the primary factor responsible for changes in the vertical position of seeds in the soil. The influence of different tillage operations has been investigated and described by models in recent years (Grundy et al, 1999;Colbach et al, 2000;Mohler et al, 2006;Spokas et al, 2007). Based on these models, the distribution of seeds in the soil following different cultivation practices can be predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Soil tillage is the primary factor responsible for changes in the vertical position of seeds in the soil. The influence of different tillage operations has been investigated and described by models in recent years (Grundy et al, 1999;Colbach et al, 2000;Mohler et al, 2006;Spokas et al, 2007). Based on these models, the distribution of seeds in the soil following different cultivation practices can be predicted.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that implied costs of seed rains are likely upper limits, because the model does not account for seed dormancy, burial depths that are suboptimal for emergence, and postdispersal seed mortality. Future studies that combine this study's bioeconomic model with models that project seed fates and movements (e.g., Renton et al 2008;Spokas et al 2007) will enable detailed understanding of economic consequences of tall morningglory seed rains. Rogers (2003) indicated that the decision to adopt a new practice is a multistage process that often begins with recognition of the need for change.…”
Section: Et Al 2016) Model Results Indicated That Crop Yieldmentioning
confidence: 99%
“…On an annual basis, we should expect the decay constants for tilled plots to be greater than for NT conditions because of increased aeration and soil residue mixing. However, predicting the decay constant may be a more complex task especially shortly after tillage, because of short‐term changes in soil moisture and temperature (Stevenson & Cole, 1999) as well as complex soil particle movement during tillage (Spokas et al , 2007). Higher soil gas diffusion and convection rates after tillage should cause immediate reductions in soil moisture (Fortin et al , 1996; Ellert & Janzen, 1999; Calderon & Jackson, 2002; La Scala et al , 2006) that could limit microbial activity resulting in a smaller decay constant.…”
Section: Resultsmentioning
confidence: 99%